Perilaku inovatif - Soebardi, Rusdijanto (Konsorsium Psikologi Ilmiah Nusantara, 2012)
Innovative work behavior has the aim to improve the performance and competence of the organization in achieving its goal. As a perspective of organizational behavior, the innovative work behavior is the interaction between the individual, group process and organizational processes, which affects the range of leadership behaviors and performance expectations of employees when the realization of innovative work behavior is completely done. The purpose of this study was to test the effect of leadership behavior through the mediation of performance expectations, in revealing the individual’s innovative work behavior. The population study was a group of companies on transportation and logistics business lines involving 199 employees. One is a holding company and the other nine are affiliate companies. Sampling design used is Proportionate Stratified Random Sampling. Measurements used De Jong-IWB (Innovative Work Behavior). Data collection and analysis of research data used path analysis. The results showed the value of total effect = 0.47 which suggests that there is direct or indirect effect between leadership behavior, and the performance expectations of innovative work behavior as a mediator.